Vapour source and spatiotemporal variation of precipitation isotopes in southwest Spain - Kohfahl, Claus; Fonseca Rodríguez, Rolf; Ruiz Bermudo, Fernando; Vadillo-Pérez, Iñaki (Wiley, 2021)
The δ2H and δ18O composition of 77 precipitation samples collected between January 2014 and April 2019 from two sites across the Guadalquivir Basin, SW Spain, were analysed. The first site is located in an urban area of Seville at 100 km distance to the Atlantic coast and the second site is located in a dune area of the Doñana National Park a few kilometres from the coast. Sampling was performed within intervals of at least 14 days if rain occurred but frequently intervals were lon- ger according to the rainfall incidence. Samples from both sites are available for the period February 2016 to June 2018 with six samples containing identical rain events at both locations. Precipitation weighted averages and local meteoric water lines pro- duced by weighting and non-weighting regression methods are presented for its use in hydrological applications. Results show a remarkably high variability in δ2H and δ18O values and precipitation weighted average d-excess values of 11.8‰ and 13‰ at the sites Plaza de España and Doñana, respectively. Temperature and amount effects were found to be weak. A significant influence of secondary evaporation for single rainfall events during summer was identified by enriched isotopic signatures with reduced d-excess values plotting close or below the global meteoric water line. Backward trajectory analysis of 115 days with daily rainfall above 3 mm yield a pre- dominant Atlantic Ocean vapour source with negligible Mediterranean influence and therefore, d-excess variability is attributed to the different ocean surface conditions of relative humidity and sea surface temperature. Parallel sampling indicate very simi- lar isotopic signatures at both sites and point to the existence of thermal effects of the Plaza de España site in Seville city during the summer season.
Keywords: Precipitación atmosférica - Guadalquivir (Cuenca hidrográfica); Deuterium excess; Hysplit backward trajectories; Local meteoric water line; Precipitation isotopes; Secondary evaporation; Spain; Temperature effect